2023
DOI: 10.3389/fmars.2023.1042799
|View full text |Cite
|
Sign up to set email alerts
|

Desalination effects on macroalgae (part b): Transplantation experiments at brine-impacted sites with Dictyota spp. from the Pacific Ocean and Mediterranean Sea

Abstract: Desalination residual brines are mostly discharged to marine environments, which can produce osmotic stress on sensitive benthic organisms. In this investigation, we performed transplantation experiments nearby desalination plants using two brown macroalgae species from a cosmopolitan genus: Dictyota kunthii (Chile) and Dictyota dichotoma (Spain). Parameters related to photosynthetic activity and oxidative stress were evaluated at 3 and 7 days for D. kunthii, and 3 and 6 days for D. dichotoma; each at 2 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Brine effluents are characterized by a salinity concentration that can double the salinity of the seawater body; this excess salinity also implies higher density (Mezher et al, 2011;Panagopoulos et al, 2019). Therefore, the discharges have been observed to mainly affect the benthic communities present in the affected area, mainly sessile communities or those with a low mobility capacity to escape from the high salinity influenced zone (Petersen et al, 2018;Sharifinia et al, 2019;Sola et al, 2020b;Muñoz et al, 2023). However, scientific experiences have demonstrated that it is possible to achieve long-term sustainable desalination when properly corrective and preventive measures are adopted (Sola et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Brine effluents are characterized by a salinity concentration that can double the salinity of the seawater body; this excess salinity also implies higher density (Mezher et al, 2011;Panagopoulos et al, 2019). Therefore, the discharges have been observed to mainly affect the benthic communities present in the affected area, mainly sessile communities or those with a low mobility capacity to escape from the high salinity influenced zone (Petersen et al, 2018;Sharifinia et al, 2019;Sola et al, 2020b;Muñoz et al, 2023). However, scientific experiences have demonstrated that it is possible to achieve long-term sustainable desalination when properly corrective and preventive measures are adopted (Sola et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the latter, the potential detrimental effects of desalination have been observed to be mainly associated with the osmotic stress caused by salt excess (e.g. Del Pilar Ruso et al, 2015;De la Ossa Carretero et al, 2016;Cambridge et al, 2019Ferna ́ndez-Torquemada et al, 2019Rodrı ́guez-Rojas et al, 2020;Panagopoulos and Haralambous, 2020a;Panagopoulos and Haralambous, 2020b;Sandoval-Gil et al, 2022;Muñoz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, in short-term-controlled laboratory conditions, we compared photosynthetic activity and oxidative stress response in the Dictyota species under increased salinity levels similar to those found nearby brine discharges. In a complementary article (Muñoz et al, 2023), similar parameters were assessed in these species under transplantation experiments in desalination plant-impacted sites.…”
Section: Introductionmentioning
confidence: 99%